MOTIVASI MAHASISWA MENJADI WIRAUSAHA PADA PROGRAM STUDI PENDIDIKAN EKONOMI - Fauzi, stkiptap (JURNAL EDUCATION AND DEVELOPMENT, 2016)
The aim of this research was to know whether there was the influence of entrepreneurship subject on studentsâ motivation to be an entrepreneurship of Economic Departement. The background of this research was to know how the influence of entrepreneurship subject on studentsâ motivation to be an entrepreneurship. Respondent of this research was 100 students which taken by using purposive sampling. The approach of this research was qualitative by applying descriptive method and questionnaire was used to collect the data. The research showed that entrepreneurship subject which included extrinsic and intrinsic factors gave influence on studentsâ motivation to be an entrepreneurship.